Os recursos hídricos da Bacia Hidrográfica do Igarapé Matafome (BHIMF), Belém-PA: características e propostas para uso e proteção - SANTOS, Marilia do Ó Teixeira (2018)
The area of the Mata Fome basin was studied for its water resources. Te surface water and groundwater in the basin have been studied in their physicalchemical aspects. The quality of the water from the stream of Mata Fome is quite damaged by human activities related to occupation of the physical environment of the basin area. Groundwater. also showed inappropriate for human consumption, since in all samples, at least one of the parameters showed results outside the range permitted by Ordinance No. 518/04 of the Brazil Ministry of Health, indicating sources of contamination. The geometric pattern of behavior of the groundwater flows shows that there are two areas of the aquifer hydraulic discharge. One of them is located in the northeast of the northern area and the other in the southwest. An area of aquifer recharge than appears on the NW sector of the studied area. For the Piper diagram, the groundwater samples are predominantly sodium and chloride, with affinity mixed and sulfides. These samples were also classified as soft water hardness. For several criteria shown throughout the study, the choice of groundwater is justified as the best way to solve the problems of supplying the residents of the Mata Fome basin.